FAKTOR YANG BERKAITAN DENGAN KEJADIAN STUNTING DI DESA GUNUNG MAKMUR KABUPATEN TANAH LAUT - Fahriani, Fahriani; Maisarah, Maisarah; Sijabat, Ruth Hidayani; Virgianti, Risa; Purwanti, Eni (LPPM Universitas Sari Mulia, 2025)
Background: Stunting is a nutritional problem for toddlers with a picture of growth failure that accumulates before and after birth, which is caused by inadequate nutritional intake. In 2022, the prevalence of stunting in South Kalimantan was 24.6%. Tanah Laut Regency is in 6th place at 26.6%. At the Takisung Community Health Center in July 2024, there were 22 stunted toddlers consisting of 11 stunted toddlers and 11 very stunted toddlers. Objective: The aim of this research is to determine the factors correlated to the incidence of stunting in Gunung Makmur Village, Tanah Laut Regency. Method: This type of research is quantitative research with a cross-sectional design. 24. The population in this study was 10 people. The number of samples was 10 people with a total sampling technique. The instrument uses a questionnaire. Data analysis used the chi-square test. Results: From the research results, it was found that there was a correlation between exclusive breastfeeding (p=0.005), dietary habit (p=0.000) and rest patterns (p=0.001) with the incidence of stunting in Gunung Makmur Village 2024. However, there was no correlation between immunization (p=0.751) and the incidence of stunting in Gunung Makmur Village 2024. Conclusion: There was a correlation between exclusive breastfeeding, dietary habit and rest patterns and the incidence of stunting in Gunung Makmur Village. Makmur 2024. On the other hand, there is no correlation between immunization and the incidence of stunting in Gunung Makmur Village in 2024. Keywords: Stunting, exclusive breastfeeding, dietary habit, rest patterns and immunization